Local Superior Products in Agricultural Sector: A case study in Banggai Regency Indonesia - Layoo, Nurhidayah; Rahman, Wahyudin; K. Djawa, Sutrisno; Mambuhu, Nurmawati; Gifari Sono, Moh.; Abd Rahim, Mustafa; Rosilawati, Ratmi; Samaduri, Lutfi; Ramlan, Winarto; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
The optimization of LSP aims to increase employment opportunities, regional economic growth, Own-Source Revenue, as well as regional per capita income, and ultimately cut the poverty. To achieve so, the findings from the research are required to determine the LSP of Banggai Regency, set the priority scale fromÂ  agriculture sectors based on the availability of raw material, market potential, human resource support, uniqueness, and economic contribution. The research used purposive sampling by selecting 15 SMEs sub-jects. The expert group consisted of 3 heads of division in Food Crops Horticulture and Plantation Department and 5 academics from Faculty of Agriculture. The researchers carried out the data collection by conducting in-depth interview to small business owners and FGD on the expert group. The result shows that the superior products of Banggai Regency are rice, corn, cassava, coconut, and banana products. The government should actively encourage the SMEs to prioritize the LSP of the coconut products. In addition, the SMEs empowerment lies in the aspects of human resource, production facilities and utilization of market potential.Â